Selected conference proceedings (MCT & Associates Limited Port of SpainTT, 1993)
Looks at issues of structural adjustment and stabilization and the appropriateness of these programmes for developing countries such as ours. Sees the programmes as being deficient and biased against the growth policies espoused by the majority of developing countries and constitute the major causes of the slowdown of economic activity, higher levels of unemployment and deterioration in living standards. Stresses that it is imperative for a Caribbean alternative to these externally originated programmes be found.
Additional copy located in the Office of the Secretary-General